The Relationship of Job Stress and Job Satisfaction with Organizational Commitment in Environmental and Occupational Health Staff Working in Alborz and Ahvaz Jundishapur Universities of Medical Sciences - Amin Torabipour; Seyed Mehdi Emamyanfard; Mohammad Veysi Sheykhrobat; Maghsoud Jafarinia (Kerman University of Medical Sciences, 2019)
The Relationship of Job Stress and Job Satisfaction with Organizational Commitment in Environmental and Occupational Health Staff Working in Alborz and Ahvaz Jundishapur Universities of Medical Sciences     Torabipour Amin1, Emamyanfard Seyed Mehdi2, Veysi Sheykhrobat Mohammad2, Jafarinia Maghsoud3 1. Assistant Professor, Department of Health Services Management, School of Public Health, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran 2. MSc Student of Health Services Management, Student Research Committee, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran 3. MSc of Environmental Health Engineering, Department of Environmental Health Engineering, School of Public Health, Alborz University of Medical Sciences, Karaj, Iran *Correspondence: Department of Health Services Management, School of Public Health, Ahvaz Jundishapur University of Medical Sciences, Golestan Boulevard, Ahvaz, Iran Tel: 00986136228553                                               Email: mehdiemamyan@gmail.com   Abstract: Background & Objectives: Environmental health professionals are among the most important sources of health system in the health sector. Issues such as job stress and job dissatisfaction can have an adverse effect on organizational commitment of health personnel. The purpose of this study was to investigate the relationship of job stress and job satisfaction with organizational commitment in environmental and occupational health professionals working in Alborz and Ahvaz Jundishapur Universities of Medical Sciences. Methods: This cross-sectional, descriptive-analytical study was performed on 238 occupational health and environmental health staff. Data were collected using Osipow Job Stress Scale, Ellen Meyer's Organizational Commitment, and Susan Job Satisfaction questionnaires.  In this study, t-test, two way ANOVA and linear regression analysis were used to determine the factors affecting organizational commitment. Data were analyzed through SPSS statistical software version 22. Results: The majority of the studied subjects were women (75.5% of environmental health staff and 81.5% of professional occupation staff).  Among the dimensions of organizational commitment, continuous commitment obtained the highest score among employees of Environmental Health (30.19 ± 6.15) and Occupational Health (27.55 ±7.49). Job satisfaction had a strong significant relationship with the three dimensions of organizational commitment (P<0.01). Conclusion: Through teaching stress management skills and increasing job satisfaction in these occupational groups, organizational commitment could be improved.   Keywords: Job Stress, Organizational Commitment, Job Satisfaction, Environmental Health, Occupational Health, Staff   Citation:  Torabipour A, Emamyanfard SM, Veysi Sheykhrobat M, Jafarinia M. The Relationship of Job Stress and Job Satisfaction with Organizational Commitment in Environmental and Occupational Health Staff Working in Alborz and Ahvaz Jundishapur Universities of Medical Sciences. Journal of Health Based Research 2019; 5(2): 215-33. [In Persian]